AN ANALYSIS OF THE STUDENTS’ DIFFICULTIES IN READING COMPREHENSION (A STUDY CONDUCTED AT SMA NEGERI 3 TONDANO) - Kokalo, Nurhikmah; Tuerah, Ignatius J.; Posumah, Jennie (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The aim of this research was to analyse and to find out the result of analysed that had conducted and to describe the student's difficulties in reading comprehension, reason of the difficulties and the solution for the difficulties encounter in reading comprehension. The research used qualitative descriptive method to describe the detail about the student's difficulties in reading comprehension. The instrument the researcher used in this research were the questionare, observation, interviewed, and documentation. The findings of this research were that researchers found several students' difficulties in understanding reading, namely difficulty understanding the meaning of the words, difficulty understanding sentence length, difficulty understanding the main idea, difficulty understanding grammar, and difficulty making conclusions. Therefore, to increase their vocabulary and understanding, students should learn words. They should also practice diligently and study English-language literature. To help the pupils become more proficient text readers, teachers should provide them different reading exercises.